2018
DOI: 10.4103/jios.jios_103_17
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Study of Three Journals of Orthodontics: A Comparative Analysis of 10 years

Abstract: The objective of this study was to conduct a comparative analysis of profiles of three esteemed journals of orthodontics: The American Journal of Orthodontics and Dentofacial Orthopedics (AJODO), the Angle orthodontist (AO), and collate it with the Journal of Indian Orthodontic Society (JIOS) from 2008 to 2017. Materials and Methods: A cross-sectional observational study was conducted, where all the issues of JIOS, AO, and AJODO were hand searched from 2008 to 2017 for specifications such as study design, auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…It was seen that the magnitude of the articles were of multiple authors from different private educational institutes emphasizing the importance of teamwork for the research/survey as well as its coverage. Similar results were also described by the previous bibliometric studies done by Thanukodi 39 , Thanuskodi 40 and Chatterjee 6 . One possible reason may be that the educational institutes encourages more of research work as a part of the postgraduate course.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was seen that the magnitude of the articles were of multiple authors from different private educational institutes emphasizing the importance of teamwork for the research/survey as well as its coverage. Similar results were also described by the previous bibliometric studies done by Thanukodi 39 , Thanuskodi 40 and Chatterjee 6 . One possible reason may be that the educational institutes encourages more of research work as a part of the postgraduate course.…”
Section: Discussionsupporting
confidence: 91%
“…Assessing the research activity is significant in carrying out proper planning and policy making. In 1969 Pritchard initially described bibliometrics as “the application of mathematical and statistical methods applied to categorize books and other media of communication.” It chiefly concerns the analytical process of metadata elements as the author(s), the publication place, the associated subject keywords, and the citations 5 , 6 . It is a statistical tool which shows quantitatively the analysis of written publications.…”
Section: Introductionmentioning
confidence: 99%
“…3 In general, JIOS is still far behind American Journal of Orthodontics and Dentofacial Orthopedics (AJODO), Angle Orthodontist (AO) , and European Journal of Orthodontics (EJO) in the number of publications per annum. 2, 4-8 This is understandable given the fact that JIOS is relatively a new journal and publishes less issues and articles per year. Reduced visibility, lower citation metrics, and not being indexed in Medline/PubMed could be other factors that reduce the number of submissions to the journal and indirectly the output.…”
Section: Discussionmentioning
confidence: 99%
“…A recent editorial in the journal reported that it receives nearly 250 submissions per year, 1 and this number is on a constant rise. A bibliometric analysis of articles from 2008 to 2017 2 found the proportion of original articles, case reports, and systemic reviews to be 55.3%, 39.9%, and 4.8%, respectively. For the articles published between 2011 and 2016, the data from Gyawali et al 3 indicate that the proportion of original articles and case reports were 55.3% and 19.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation